Réponses

2013-04-21T17:55:51+02:00

Bonjour,

 

a)A = \left(3x-1\right)\left(2x+5\right)-\left(3x-1\right)^2\\ A = 6x^2+15x-2x-5-9x^2+6x-1\\ A = -3x^2+19x-6

 

b)A = -3x^2+19x-6\\ A = -3\left(\sqrt 2+1\right)+19\left(\sqrt 2+1\right)-6\\ A = -3\left(3+2\sqrt 2\right)+19\sqrt 2 +13\\ A = 4+13\sqrt 2

 

c)A = \left(3x-1\right)\left(2x+5\right)-\left(3x-1\right)^2\\ A = \left(3x-1\right)\left[\left(2x+5\right)-\left(3x-1\right)\right]\\ A = \left(3x-1\right)\left(-x+6\right)

 

d)x = 6 :

 A = \left(3x-1\right)\left(-x+6\right)\\ A = \left(18-1\right)\left(-6+6\right) = 0\times 17 = 0

 

x=1/3

 A = \left(3x-1\right)\left(-x+6\right)\\ A = \left(3\times \frac 13 -1\right)\left(-\frac 13+6\right)\\ A = \left(1-1\right)\left(-\frac 13 +6\right)\\ A = 0

2013-04-21T17:56:03+02:00
A=(3x-1)(2x+5)-(3x-1)^2
a) A=6x^2+15x-2x-5-(9x^2-6x+1)
A=6x^2+13x-5-9x^2+6x-1
A=-3x^2+19x-6

b) A=-3(V2+1)^2+19(V2+1)-6
A=-3(2+2V2+1)+19V2+19-6
A=-6-6V2-3+19V2+19-6
A=13V2+4

c) A=(3x-1)(2x+5-3x+1)
A=(3x-1)(-x+6)

d) A=(3*6-1)(-6+6)
A=17*0=0

A=(3*1/3-1)(-1/3+6)
A=(1-1)(-1/3+6)=0